2014
DOI: 10.1128/ec.00031-14
|View full text |Cite
|
Sign up to set email alerts
|

The Entamoeba histolytica Dnmt2 Homolog (Ehmeth) Confers Resistance to Nitrosative Stress

Abstract: c Nitric oxide (NO) has antimicrobial properties against many pathogens due to its reactivity as an S-nitrosylating agent. It inhibits many of the key enzymes that are involved in the metabolism and virulence of the parasite Entamoeba histolytica through S-nitrosylation of essential cysteine residues. Very little information is available on the mechanism of resistance to NO by pathogens in general and by this parasite in particular. Here, we report that exposure of the parasites to S-nitrosoglutathione (GSNO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…The QRT-PCR values were normalized to the level of rDNA74. Data are expressed as the mean ± SD of three independent experiments.…”
Section: Figurementioning
confidence: 99%
“…The QRT-PCR values were normalized to the level of rDNA74. Data are expressed as the mean ± SD of three independent experiments.…”
Section: Figurementioning
confidence: 99%
“…Overexpression of dDnmt2 promoted longevity that was accompanied by resistance to oxidative stress (paraquat treatment) and upregulation of small heat shock proteins, namely Hsp22, Hsp23, and Hsp26 (Lin et al, ). Overexpression of another Dnmt2, namely Ehmeth, also conferred resistance to HP treatment and nitrosative stress ( S ‐nitrosoglutathione stimulation) and caused upregulation of heat shock protein 70 in the protozoan parasite E. histolytica (Fisher et al, ; Hertz et al, ). Moreover, oxidative stress‐induced Dnmt2 upregulation was observed in different human and mouse cell lines with unmodified physiological levels of Dnmt2 (Lewinska, Wnuk et al, ; Mytych et al, ; Mytych, Zebrowski, Lewinska, & Wnuk, ; Thiagarajan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…HP‐treated Dnmt2‐silenced fibroblasts were also more prone to apoptosis than control cells (this study) and Dnmt2 may be considered as a pro‐survival signal during stress conditions. Dnmt2‐mediated resistance to stress conditions is associated with high levels of tRNA Asp methylation in Drosophila and E. histolytica (Hertz et al, ; Schaefer et al, ). It has been shown that Dnmt2‐mediated tRNA methylation protected tRNAs against stress‐induced cleavage in Drosophila (Schaefer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the tRNA modification 2’‐0‐cytosine methylation (Cm) was shown to be increased in response to pathogen infection in Arabidopsis (Ramirez et al ). In other organisms, several tRNA modifications were shown to be induced under stress conditions such as oxidative stress (Chan et al ; Chan et al ), nutrient starvation (Preston et al ) and toxins (Hertz et al ).…”
Section: Plant Transfer Rna Modifications and Their Functionsmentioning
confidence: 99%